O sistema de armas de Artilharia de Campanha nacional em 2030 - Costa , André Filipe Coelho (2017)
Submitted by Academia Militar (ferreira.pap@mail.exercito.pt) on 2017-11-09T15:17:42Z No. of bitstreams: 1 TIA_Asp_Art_A.Costa.pdf: 2342601 bytes, checksum: e0932ab9d806b22820a8b299d1686386 (MD5)